Lo que no está escrito - Freijo Corbeira, Aurora (Bollettino Filosofico, 2016)
In order to be a witness, it is necessary to speak. To say not just any word, but a “minor” word, in the manner of Deleuze, one which deterritorializates, one which stands on its own, as Gadamer says, one which speaks truth. That word, which for many is the poetic word, necessarily becomes a political word, and it needs to be delivered from “outside the palace”, according to Pasolini, in the outskirts of power. Such are the words of Agamben —which know of nacked lives—, of Pasolini —which recognize the lights of resistance of the fireflies—, ambiguous words of Herta Müller, and the decolonial ones of Césaire. All of them call to not forget the existence of a inclusive exclusion in our societies, and in the end, of an Auschwitz before and after Auschwitz. Speaking in the manner of liberated Theseus or contemporary Zarathustras, they point to an sphere of resistance, of sacredness, and they summon us to a kind of community, that of the friends of solitude, as Derrida would say, where dwells the memory of barbarians, strangers, and fireflies.